ANALISIS PERMODELAN SUB DAS PADA DAERAH ALIRAN SUNGAI KRUENG PASE KABUPATEN ACEH UTARA - Rahmawati Rahmawati; Eldina Fatimah; Masimin Masimin (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Watershed management can be started by evaluation how the response of watershed hydraulic toward rainfall and become run off that will flow downstream. Transformation of rain into flow is a method used to find out effect of land use change and its parameter toward flow hydrograph. Watershed Kr. Pase is one of  most rapid reduction of forest area. Land use change occurred in this watershed affecting discharge amount of run off which required further calculation. This calculation using the rational method by calculating rainfall intensity parameter (I),watershed area (A), and flow coefficient (C) in watershed. Data of land use provide in this study are on year 2007, 2013, and 2017 which will examine watershed Kr. Pase into subwatershed model, whereas from map analysis obtained three subwatersheds. After some calculation off run off discharge at watershed Kr. Pase, than it is use sub-watershed with longest concertration time (tc).